714. Increase in Multidrug-resistant Salmonella Serotype I 4, [5], 12:i:- Infections Linked to Pork—United States, 2009–2018. (31st December 2020) - Plumb, Ian D; Brown, Allison C; Stokes, Erin K; Chen, Jessica; Tolar, Beth; Sundararaman, Preethi; Folster, Jason; Carleton, Heather; Friedman, Cindy R
Abstract: Background: Salmonella enterica I 4, [5], 12:i:- is the 5 th most common serotype causing clinical Salmonella infections in the United States. A strain with resistance to ampicillin, streptomycin, sulfamethoxazole, and tetracycline (ASSuT) has been linked to swine production in Europe and the United States. We reviewed U.S. surveillance data to describe clinical infections with antibiotic-resistant I 4, [5], 12:i:-. Methods: We reviewed data from CDC's National Antimicrobial Resistance Monitoring System (NARMS) from 2009–2018 to describe trends. We analyzed whole-genome sequence data in PulseNet, the molecular surveillance network for foodborne illness in the United States, from 2015–2018 to distinguish between strains of I 4, [5], 12:i:- using core-genome multilocus sequence typing, and identified antibiotic resistance determinants (ARDs). We reviewed data from the Foodborne Disease Outbreak Surveillance System to identify foods associated with outbreaks during 2009–2018. Results: From 2009–2013 to 2014–2018, I 4, [5], 12:i:- increased as a proportion of nontyphoidal Salmonella isolates in NARMS from 4.3% to 5.0% (P=0.006), while I 4, [5], 12:i:- resistant to ASSuT increased from 1.1% to 2.6% (P< 0.001). Of the 3, 056 sequenced I 4, [5], 12:i:- isolates in PulseNet, 2, 105 (69%) were in a clade within 0–108 alleles of each other (ASSuT clade). Within this clade, 77% of isolates had ARDs conferring resistance to ASSuT, compared with 3% outside the clade. Isolates in the clade were also more likely than those outside the clade to have ARDs conferring decreased susceptibility to ciprofloxacin (13.1% vs. 5.2%, P< 0.001) and resistance to ceftriaxone (5.4% vs. 2.3%, P< 0.001). Among I 4, [5], 12:i:- outbreaks with a single food source, those related to the ASSuT clade were more often linked to pork (10/15 [67%] vs. 1/5 [20%], P=0.07). Conclusion: The increase in I 4, [5], 12:i:- infections during 2009–2018 was likely driven by a clade of which most members had resistance to ASSuT, and many had decreased susceptibility to antibiotics used for empiric treatment. The association of this strain with outbreaks linked to pork suggests that measures to decrease carriage of Salmonella and selection for this strain in swine could prevent clinical infections with multidrug resistant Salmonella I 4, [5], 12:i-. Disclosures: All Authors : No reported disclosures